FINLAND’S NATIONAL MEDIATION COOPERATION - Coordinating Mediation Networks From the Public Officials Perspective - Vesterinen, Heini (My University, 2016)
Mediation field has become more complex with various non-official actors. Thus, better coordination is needed to avoid the competition and overlaps, and to benefit from the complementarity. The topic is particularly timely due to the current refugee crises and recent cuts in development cooperation appropriation. This thesis studies the mediation cooperation between different Finnish actors. The aim of the thesis is to gain a comprehensive understanding of the mediation field in Finland and find the gaps between best practices and the actual situation. Furthermore, to provide concrete recommendations for improving the functionality and coordination of the mediation networks. The study attempts to answer the question how to manage mediation networks in Finland? The primary beneficiary of the study is the Ministry for Foreign Affairs of Finland (MFA). Mediation is one of the most cost effective, efficient and sustainable conflict prevention and resolution methods. It is a source of international political power and public diplomacy. Furthermore, it offers a small nation an opportunity to influence and build relationships with the leading nations. The best results in mediation are gained with networked model. Government has a significant role in fostering mediation structures and capacity. This qualitative study applies theme interview research method. The sample group consists of seven people who represent various positions within the governmental and non-governmental organizations that operate in the field of mediation. The sampling represents a methodological mix that combines elements from intensity, purposeful and snowball sampling. The primary research data was collected in year 2015 with interviews that lasted averagely 50 minutes. Finland is profiled as a developer of mediation structures and coordination. However, the findings reveal, that on a national level mediation networks are not properly institutionalized or coordinated. The existing expertise and capacity are not fully utilized. The lack of awareness reflects to the political will, hence, resources are allocated insufficiently to mediation efforts or to mediation capacity development. This results in competition, insufficient information sharing and availability, inconclusive coordination, and non-functional mediation structures. At the moment, the MFA manages mediation networks mainly with funding procedures. If Finland wants to be an internationally recognized mediation actor there is a need for development. The best attempt from the MFA to manage mediation networks is the national Coordination Group on Mediation (CGM). However, it is a powerless unofficial body that should be more systematic and have clear goals. The most attainable solution is to develop CGM and take advantage of information technology to overcome the challenges, to improve standards in mediation work, to benefit from the complementarity, and to manage the complexity in the field of mediation.
Keywords: Mediation; Network model; Ministry for Foreign Affairs of Finland; peace work cooperation; conflict prevention; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|